Impact of milling on the functional and physicochemical properties of green lentil and yellow pea flours. Issue 1 (4th December 2021) - Guldiken, Burcu; Franczyk, Adam; Boyd, Lindsey; Wang, Ning; Choo, Kristin; Sopiwnyk, Elaine; House, James D.; Paliwal, Jitendra; Nickerson, Michael
Abstract: Background and objectives: Pulse flours with different particle sizes are available for food production. The effect of varying milling techniques on the quality characteristics of green lentil (GL) and yellow pea (YP) flours was investigated. Findings: Using a Ferkar mill (one‐step vertical knife mill) caused wider distribution and bigger particle size in all flours than milling with a roller mill. The highest starch damage (3%), starch content (57%), but lowest protein content (22%) were found in YP break flours produced by roller milling. Foaming stability of pulse flours decreased to 51%–71% after 120 min. Lowest viscosities were determined in Ferkar milled flours during pasting. There was no difference in protein strength of GL flours; however, starch gelatinization was found the highest in Ferkar milled flours. In vitro starch digestibility and in vitro protein digestibility‐corrected amino acid score were not affected from milling type within each pulse type. Conclusion: Different flour streams and different milling technologies caused changes in various flour characteristics. However, the particle size of roller mill flours was similar in each pulse type. Significance and novelty: The obtained results are a crucial step in better understanding the functional properties and possible food applications of pulse flours according to different milling streams and particle sizes.